2015
DOI: 10.1155/2015/248678
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pneumococcal Conjugate Vaccine on Pediatric Tympanostomy Tube Insertion in Partial Immunized Population

Abstract: Objective. To investigate the impact of seven-valent pneumococcal conjugate vaccine on tube insertions in a partial immunized pediatric population. Study Design. Retrospective ecological study. Methods. This study used Taiwan National Health Insurance Research Database for the period 2000–2009. Every child under 17 years old who received tubes during this 10-year period was identified and analyzed. The tube insertion rates in different age groups and the risk to receive tubes in different birth cohorts before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The remaining 5 studies 10,11,13,16,21 were included in the qualitative analysis. In 3 studies, 13,16,21 the rate of tympanostomy tube insertion was significantly decreased in the post-PCV7 period compared with the pre-PCV vaccine period.…”
Section: Tympanostomy Tube Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 5 studies 10,11,13,16,21 were included in the qualitative analysis. In 3 studies, 13,16,21 the rate of tympanostomy tube insertion was significantly decreased in the post-PCV7 period compared with the pre-PCV vaccine period.…”
Section: Tympanostomy Tube Insertionmentioning
confidence: 99%
“…The remaining 5 studies 10,11,13,16,21 were included in the qualitative analysis. In 3 studies, 13,16,21 the rate of tympanostomy tube insertion was significantly decreased in the post-PCV7 period compared with the pre-PCV vaccine period. One study 11 reported a greater reduction in the number of tympanostomy tube insertions in the PCV13 group than in the PCV7 group (HR, 0.76; 95% CI, 0.72-0.80).…”
Section: Tympanostomy Tube Insertionmentioning
confidence: 99%
“…9,10 Besides antibiotic treatment, the pneumococcal conjugate vaccine (PCV) composed of capsular polysaccharide antigens has been demonstrated to be highly effective in preventing pneumococcal disease and controlling IPDs worldwide, particularly in the developed countries. [11][12][13][14] Moreover, herd immunity, which is believed to be mediated by a reduction in the transmission of pneumococci to susceptible individuals, has been discovered as another benefit of universal PCV7 immunization programs. 14 Three PCVs, including PCV 7, PCV 10, and PCV 13, are currently available on the market, which are immunogenic and protective among children less than 2 years old.…”
Section: Introductionmentioning
confidence: 99%
“…16 We therefore consider that the dataset used herein is Prophylactic effects of PCV were examined in studies of the 10-valent pneumococcal non-typable Hemophilus influenzae protein D conjugate vaccine (PHiD-CV); most of the studies reported a reduction in the MTTI incidence by PHiD-CV. [17][18][19] Investigations conducted after the introduction of PCVs indicated that both PCV7 [8][9][10][11][12][13][14]20 and the subsequent introduction of PCV13 continued to reduce the incidence of MTTI. [21][22][23] However, most of those etiological studies were conducted based on the use of the whole data with all age groups of children.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies further suggest prophylactic effects on the onset of ROM and the incidence of MTTI caused by complex otitis media (ComOM). [8][9][10][11][12][13][14] However, little information is available about specific age groups who would receive health benefit from the prevention of ComOM that requires MTTI.…”
Section: Introductionmentioning
confidence: 99%